(untitled) (Journal of Economic Research & Business Administration, 2015)
The main purpose of the paper is to show main differences between the concept of human resource management (HRM) and the concept of personnel management. HRM should be viewed as a strategic approach to the management of the people who individually and collectively contribute to the achievement of organizational goals. The human resource management itself is characterized by hard and soft approaches. The hard approach to HRM is based on the quantitative aspects and “rational” methods. The soft approach to HRM is rooted in the school of human relations and behavioral sciences based on communication, theories of motivation and leadership concepts. The basic idea of the soft approach is to achieve the employee commitment to business objectives to involve them in creating the favorable environment for communication and information exchange and organizational culture. Despite of using “hard” approach to HRM in some Kazakhstani organizations there is no clear understanding discrepancy between these two concepts. The strategic orientation of the concept is developed in the model of David Gest and The Harvard Map of Michael Beer. Using these models and also “soft” approach would let the Kazakhstani management become more effective.